PENERAPAN PENDEKATAN KONTEKSTUAL KEMAMPUAN PEMAHAMAN MATEMATIS SISWA SMP KELAS VII-B PADA MATERI PERSAMAAN LINEAR SATU VARIABEL - Ranti Nursyifa Jannah; Eka Senjayawati (IKIP Siliwangi, 2023)
This study aims to determine the improvement of students' mathematical understanding skills on the One Variable Linear Equation (PLSV) material. This type of research is Classroom Action Research (CAR) with the subject of this research are 15 students of class VII in one of the junior high schools in Cimahi who have a Minimum Completeness Criteria (KKM) of 7.00. In this study, the instrument used was 5 about the material of One Variable Linear Equation (PLSV) which focused more on mathematical understanding ability, then conducted an initial test before the action (pretest), and the second test after giving the action (posttest). The data collection technique in this study was 5 test questions, then the score data on the pretest and posttest were tested for the difference between the two averages. The results of this study indicate that aspects of students' mathematical understanding abilities have increased which can be seen from the questions tested on each test. Based on the results of the study, it can be concluded that the contextual application of students' mathematical understanding abilities has a positive impact on improving student learning outcomes in the one-variable linear equation (PLSV) material.